Note—On the Validity of Marginal Analysis for Allocating Servers in M/M/c Queues - Dyer, M. E.; Proll, L. G. (Management Science, 1977)
In this note we prove a conjecture of Rolfe concerning the convexity of the expected queueing time formula for an M/M/c queue.